Transformational Leadership for Inclusive Education: Principal Strategies in Building Child-Friendly School Cultures - Nani Kurniasari; Nur Khoiri; Lilik Ariyanto (Pascasarjana Universitas KH. Abdul Chalim, 2026)
Inclusive education and child-friendly schooling are crucial components of quality primary education, yet implementing these practices effectively remains challenging, particularly in managing diverse learners with varying abilities. This qualitative descriptive study examines the principal's role in leading inclusive education programs at SDN Sawah Besar 01, Semarang. Data were collected through semi-structured interviews with the principal, two teachers, one parent, and one student, complemented by classroom observations and document analysis conducted in October 2025. Triangulation of these multiple sources ensured the credibility and comprehensiveness of the findings. The study found that the principal implemented transformational and participatory leadership in managing inclusive education through planning, organizing, implementing, and controlling functions. Key strategies included integrating inclusivity into the school vision, fostering collaboration with teachers and parents, and applying differentiated instruction. These efforts contributed to increased student participation, positive peer interactions, and a supportive learning environment. However, limited facilities, assistive devices, and the absence of a special education teacher remain significant challenges. This study contributes to the literature on educational leadership in Indonesia by demonstrating that the principal’s moral and participatory leadership is pivotal in creating a truly inclusive and child-friendly primary school environment.